2019
DOI: 10.1038/s41467-019-09397-2
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin pores permeabilize mitochondria to augment caspase-3 activation during apoptosis and inflammasome activation

Abstract: Gasdermin E (GSDME/DFNA5) cleavage by caspase-3 liberates the GSDME-N domain, which mediates pyroptosis by forming pores in the plasma membrane. Here we show that GSDME-N also permeabilizes the mitochondrial membrane, releasing cytochrome c and activating the apoptosome. Cytochrome c release and caspase-3 activation in response to intrinsic and extrinsic apoptotic stimuli are significantly reduced in GSDME-deficient cells comparing with wild type cells. GSDME deficiency also accelerates cell growth in culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
485
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 587 publications
(509 citation statements)
references
References 66 publications
23
485
1
Order By: Relevance
“…A recent study pointed out that GSDME augments the activation of the mitochondrial apoptotic pathway via forming pores in the mitochondria to facilitate cytochrome c release. 33 Other superfamily members, like GSDMA and GSDMD, seem to share the ability to augment the apoptotic pathway through mitochondria. 33,34 Therefore, more sophisticated experiments are required to further clarify the role of GSDME in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study pointed out that GSDME augments the activation of the mitochondrial apoptotic pathway via forming pores in the mitochondria to facilitate cytochrome c release. 33 Other superfamily members, like GSDMA and GSDMD, seem to share the ability to augment the apoptotic pathway through mitochondria. 33,34 Therefore, more sophisticated experiments are required to further clarify the role of GSDME in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that the apoptotic and GSDMD-mediated pyroptotic pathways activate each other or operate simultaneously under certain conditions. [36][37][38]76 (b) The amount of GSDMD pores will be influenced by the expression level of GSDMD, degree of caspase-1 activation, and regulatory mechanisms that control pyroptosis. GSDMD pores cause pyroptosis, through which the plasma membrane is perforated, leading to the robust release of IL-1β.…”
Section: Asc-dependent Caspase-8 Activationmentioning
confidence: 99%
“…However, a previous study demonstrated that GSDMD-dependent caspase-3 activation occurred in macrophages several hours after the cytoplasmic delivery of LPS and suggested that GSDMD promoted caspase-3 activation by facilitating the release of cytochrome c from mitochondria. 76 GSDMD p30 binds to cardiolipin and other phospholipids that are localized in mitochondrial membranes, which enables this pore-forming protein to permeabilize mitochondria, leading to cytochrome c release. 34,35 However, based on the essential role of small apoptosis mediators, ATP/dATP and cytochrome c, in the formation of apoptosomes, the apoptosome pathway unexpectedly continued to operate after pyroptosis.…”
Section: Inflammasome-associated Pyroptosis and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Gasdermin E is a member of a family of proteins that facilitate necrotic programmed cell death (pyroptosis) following cleavage by caspase-3 56 . Pyroptosis has recently been shown to promote knee osteoarthritis 57,58 , and upregulation of Gsdme in high-grade osteoarthritis cartilage ( Figure 5), supports a role for gasdermin E in disease progression.…”
Section: And 6)mentioning
confidence: 99%